2010
DOI: 10.1088/0004-637x/719/2/1813
|View full text |Cite
|
Sign up to set email alerts
|

A Mapping Survey of Dense Clumps Associated With Embedded Clusters. Ii. Can Clump-Clump Collisions Induce Stellar Clusters?

Abstract: We report the H 13 CO + (J=1-0) survey observations toward embedded clusters obtained using the Nobeyama 45m telescope, which were performed to follow up our previous study in the C 18 O survey with a dense gas tracer. Our aim is to address the evolution of cluster-forming clumps. We observed the same 14 clusters in C 18 O, which are located at distances from 0.3 to 2.1 kpc with 27 ′′ resolution (corresponding to Jeans length for most of our targets) in H 13 CO + . We detected the 13 clumps in H 13 CO + line e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 52 publications
(69 reference statements)
3
31
0
Order By: Relevance
“…Such a collision of GMCs triggering active star formation (including cluster formation) has already been evidenced in the Sgr B2 region (Hasegawa et al 1994;Sato et al 2000) and more recently in the Trifid Nebula (Torii et al 2011), indicating that collisions of GMCs should play a key role in cluster formation. It is interesting to note that Higuchi et al (2009Higuchi et al ( , 2010 recently presented a study of 14 dense molecular clumps associated with embedded clusters including the same objects observed in our study (i.e., Clumps 1-3 in S247). They suggested that formation of clusters associated with Clumps 1-3 was triggered by clump-clump collisions based on the analyses of the velocity structures of the clumps.…”
Section: Global Distributions Of Young Stellar Objects and Molecular supporting
confidence: 65%
“…Such a collision of GMCs triggering active star formation (including cluster formation) has already been evidenced in the Sgr B2 region (Hasegawa et al 1994;Sato et al 2000) and more recently in the Trifid Nebula (Torii et al 2011), indicating that collisions of GMCs should play a key role in cluster formation. It is interesting to note that Higuchi et al (2009Higuchi et al ( , 2010 recently presented a study of 14 dense molecular clumps associated with embedded clusters including the same objects observed in our study (i.e., Clumps 1-3 in S247). They suggested that formation of clusters associated with Clumps 1-3 was triggered by clump-clump collisions based on the analyses of the velocity structures of the clumps.…”
Section: Global Distributions Of Young Stellar Objects and Molecular supporting
confidence: 65%
“…This scenario is also suggested by recent studies of the global dynamics of Serpens and other star-forming regions (e.g. Higuchi et al 2010;Schneider et al 2010;Galván-Madrid et al 2010). …”
Section: Introductionsupporting
confidence: 66%
“…There has been discussion that collisions between the interstellar molecular clouds may trigger the star formation (e.g., Loren 1976;Higuchi et al 2010;Duarte-Cabral et al 2011). Many of the previous studies reported discoveries of pairs of molecular clouds having velocity separations of a few km s −1 .…”
Section: Previous Studies On CCCmentioning
confidence: 99%